HUBUNGAN KOORDINASI MATA DAN KAKI DENGAN KETERAMPILAN SEPAK SILA PERMAINAN SEPAK TAKRAW PADA TIM PUTRA MAN 1 KAMPAR - Roza, Andi; Zainur, Zainur; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Sila is a fundamental technique in the game of sepak takraw because the effort to play the ball is carried out by the player, both tekong and wedge control the ball that aims to make passes and provide feedback, both himself and to friends in an effort to attack the opponent. The basic technique of precepts. Judging from observations and observations during training in the field, there are several problems, one of which is when feeding the ball to the smasher is often not optimal and does not match the desired expectations, even though the technique of baiting and soccer techniques is the thing that must be mastered by a player sepak takraw. The population in this study were takraw Putra MAN 1 KAMPAR players as many as 10 people. By using a total sampling technique, the in this study amounted to 10 people. The instruments in this study were aye and foot coordination whit sepak sila abilities. Data obtained were analyzed using moment product correlation. Based on the results of research and data processing using statistical research procedures, it was concluded that for the relationship of variable X with variable Y obtained r count = 0,982> r table = 0,666, then there was a relationship between variable X and variable Y, thus Ha was accepted. This means that the hypothesis is accepted at a significant level α = 0,05 in other words there is a Relationship between Eye and Foot Coordination with Sila football Skill in Sepaktakraw Games on the MAN 1 Kampar men’s ream.Key Words: Eye and Foot Coordination, Sila sepak Skills.